O ensino primário, segundo as propostas na Conferência nacional de Educação: 1965 1969 - Souza, Henrique Antonio Profili de (2011)
The research approaches the National Conference on Education in its four editions, held between 1965 and 1969, its constitutive structure, based on the analysis of its Proceedings, and of the Laws that it established and its subsequent amendments describing its organization, its participants, entities and agencies that were represented, the educational concepts of their participants, either members of government bodies or representatives of organizations and institutions - domestic and foreign, public or private. The research also carries an analysis of working papers produced by the responsible agencies and their divisions, which were used to report the state of education nationally and in each state and territory in order to establish a diagnosis of primary education in Brazil, presenting the structure and the existing shortcomings and how to reach the targets set by the National Education Plan. As an extension of the theme related to primary education, the survey also gives a brief overview of the installing of the classes of 5th and 6th grades in the city of São Paulo as part of the claims for extension of primary education that the Law of Directives and Basis for National Education of 1961 provided